Interactions between Phytophthora cactorum, Armillaria gallica and Betula pendula Roth. Seedlings Subjected to Defoliation - Justyna Anna Nowakowska (Forests, 2020)
The purpose of this study was to better understand the interactive impact of two soil-borne pathogens, Phytophthora cactorum and Armillaria gallica, on seedlings of silver birch (Betula pendula Roth.) subjected to stress caused by mechanical defoliation, simulating primary insect feeding. This is the first experimental confirmation of silver birch seedling root damage (and in consequence shoot mortality) caused by the additive effect of defoliation stress and P. cactorum inoculation via soil. However, the most severe damage to roots occurred after A. gallica inoculation. One year after treatments, chlorophyll fluorescence measurement, and gas chromatography coupled with mass spectrometry (GC-MS) were used to analyze the photosynthetic activity in leaves, the volatile organic compounds (VOCs) emitted by the birch leaves, and chemical compounds from the roots. The cumulative effect of the two pathogens and partial defoliation reduced photosynthetic activity, suggesting dysfunction of photosystem PSII due to the applied stresses. In summary, it seems that the main differences in photosynthetic performance could be attributed to Armillaria infection. The birch leaves in seedlings exposed to 50% defoliation, and inoculation with P.cactorum and A. gallica, emitted more aromatic carbonyls and alcohols, as well as half as much aliphatic esters, compared to controls. In infected birch roots, the production of phenols, triterpenes, and fatty alcohols increased, but fatty acids decreased. Higher levels of aromatic carbonyls and alcohols in leaves, as well as phenolic compounds in the roots of stressed birches (compared to control) suggest an activation of plant systemic acquired resistance (SAR).